The Role Of Knowledge Management In Strategic Directing At Tishreen University - سليطين, سوما; ناصر, أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2021)
the study has been carried out during the year 2020 at Tishreen University. The research deals the concept of knowledge management and its importance, strategic planning and its importance and their role in universities. The researcher used the following statistical methods: The arithmetic mean and standard deviation were tested using the correlation coefficient. The most important results of the research are: there is a significant relationship between knowledge management processes and the process of setting strategic direction at Tishreen University, there is a significant relationship between knowledge management processes and the process of determining the strategic vision at Tishreen University, there is a significant relationship between knowledge management processes and the process of defining the strategic message at Tishreen University, there is a significant relationship between knowledge management processes and the process of setting strategic goals at Tishreen University. It's necessary in universities to apply knowledge management because of its important role in strategic planning.